ENHANCING ORGANIZATIONAL AND ECONOMIC MANAGEMENT MECHANISMS IN INDUSTRIAL ENTERPRISES: INSIGHTS FROM AGRICULTURAL PRODUCTION - Gulsanam Boykuzieva (Scholars Digest Publishing, 2024)
This research explores the enhancement of organizational and economic management mechanisms within industrial enterprises, drawing valuable insights from the context of agricultural production. As industries evolve, the need for efficient and adaptive management becomes paramount. Through a detailed examination of agricultural production enterprises, this study identifies key strategies and practices that can be applied to optimize organizational and economic mechanisms in broader industrial settings. The research employs a multidimensional approach, combining case studies, data analysis, and theoretical frameworks to uncover the intricacies of effective management. It delves into the unique challenges and opportunities presented by the agricultural sector, offering a nuanced perspective on the transferability of successful practices to other industrial domains. Findings highlight the importance of strategic planning, resource allocation, and adaptive leadership in the pursuit of improved organizational and economic outcomes. The role of technology integration and sustainable practices in agricultural enterprises becomes a focal point, demonstrating their potential impact on industrial management at large.
Keywords: Organizational Management, Economic Mechanisms, Industrial Enterprises, Agricultural Production, Strategic Planning, Resource Allocation, Sustainable Practices, Management Strategies, Resilience, Sectoral Insights, Performance Optimization.